2012
DOI: 10.1016/j.aap.2011.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Using reflective clothing to enhance the conspicuity of bicyclists at night

Abstract: Bicycling at night is more dangerous than in the daytime and poor conspicuity is likely to be a contributing factor. The use of reflective markings on a pedestrian's major joints to facilitate the perception of biological motion has been shown to greatly enhance pedestrian conspicuity at night, but few corresponding data exist for bicyclists. Twelve younger and twelve older participants drove around a closed-road circuit at night and indicated when they first recognized a bicyclist who wore black clothing eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 13 publications
3
59
1
Order By: Relevance
“…However, night-time conspicuity improvement treatments, such as retro-reflective vests and markers, were found to produce mixed findings for motorcycles, as identified in Haque et al (2012). For bicycles, on the other hand, use of reflective vests and markers (Thornley et al, 2008;Wood et al, 2009) and ankle and knee reflectors (Wood et al, 2012) were found to be generally effective. Bicycle lights were also found to reduce crashes by increasing their visibility during daylight and twilight periods, but no such effects seen for night time (Madsen et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, night-time conspicuity improvement treatments, such as retro-reflective vests and markers, were found to produce mixed findings for motorcycles, as identified in Haque et al (2012). For bicycles, on the other hand, use of reflective vests and markers (Thornley et al, 2008;Wood et al, 2009) and ankle and knee reflectors (Wood et al, 2012) were found to be generally effective. Bicycle lights were also found to reduce crashes by increasing their visibility during daylight and twilight periods, but no such effects seen for night time (Madsen et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Increasing the conspicuity of riders and two-wheelers to improve safety has been recommended in a number of studies (Haque et al, 2012;Pai et al, 2009;Thornley et al, 2008;Wood et al, 2009;Yuan, 2000). In addition to headlight (static or blinking), reflective vest, and reflective markings on two-wheelers, researchers (Wood et al, 2012) have suggested use of ankle and knee reflectors for bicyclists. Enforcement of mandatory bicycle lights at night by imposing fines, as practised in the Netherlands (Wegman and Aarts, 2006), could discourage bicycle riding at night without lights.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies showed that wearing protective clothing reduces accident severity, presumably in collision situations (Persaud et al, 2012;Wood et al, 2012;Amoros et al, 2012;Berg and Westerling, 2007). In order to reduce the RR of bicycle accidents, a greater range of guidelines and measures are needed.…”
Section: Behaviormentioning
confidence: 97%
“…Because closed road studies allow for the repetition of orchestrated stimulus events and trials, they provide good estimates about specific driver competences as a function of visual status; for example, they can establish the distance at which a pedestrian or cyclist can be detected or a road-sign can be read. 20, 127, 152, 153 Closed-road designs can be viewed as “proof-of-concept” studies in that they demonstrate under near-laboratory, highly controlled conditions, how vision impacts performance while the participant drives and controls a real vehicle. On the other hand, closed road studies do not allow for confident generalizations to the open road where the driving environment is highly complex and often chaotic.…”
Section: Performancementioning
confidence: 99%